Mythology as a Catalyst for Creative Economy and Environmental Conservation: A Critical Comparison of the Manguni and Bali Starling Narratives - Mayske Rinny Liando; Ni Wayan Sumitri; Salmah Jan Noor Muhammad; Fince Leny Sambeka; Gerry Kadamehang (Universitas Udayana, 2026)
This study is motivated by the importance of revitalizing local values through the construction of myths that can bridge spirituality, education, and the creative economy within the context of conservation and sustainable tourism. The research focuses on how the myths of the Manguni bird and the Bali Starling are constructed and transformed as media for education, conservation, and the creative economy, including challenges encountered. Critical discourse analysis, social construction and eco-biology theory are employed to interpret these phenomena. Data were collected through observation, interviews, and document analysis. The findings reveal that bird mythology in Bali and Minahasa communities both is constructed within local narratives and transformed into a medium for ecological ethics education, creative innovation, and ecotourism development. These findings emphasize the importance of policies that integrate such strategies into the management of ecotourism, and encourage the adoption of a development paradigm rooted in cultural authenticity.